Report on the workshop on barriers to the application of forestry research results - Nair, C.T.S.; Enters, T.; Payne, B. (Center for International Forestry Research, 1995)
Despite the increase in forestry research investment, the scientific base of forestry field practices remain weak, primarily due to the barriers to the application of research results. While barriers become visible at the application stage, their origin could be traced to all the preceding stages, including problem identification, research process and communication and extension. Mechanisms for identification of researchable problems, especially through the involvement of users are at best weak. The problem is further aggravated due to compartmentalized research, failure to incorporate local technical know-how and weaknesses in research management including inappropriate evaluation systems. A substantial proportion of research results are not communicated to potential users, but directed at other researchers. Even when relevant results are made available, they may remain unutilized as potential adopters may have objectives not taken into account while designing research. Also forestry services geared to enhance revenue in the short term may fail to take cognizance of the long term benefits from the adoption of improved practices.